PENGARUH PEMBERIAN SEDUHAN TEH DAUN SIRSAK (ANNONA MURICATA LINN) TERHADAP PENURUNAN KADAR ASAM URAT PADA LANSIA DI POSYANDU KENANGAN BARU - Irene Larva Dei Sitorus; Lam Murni Sagala (Universitas Murni Teguh, 2026)
Gout is a degenerative disease commonly experienced by the elderly as a result of purine metabolism disorders. It is characterized by elevated uric acid levels in the blood, causing joint pain and a decline in quality of life due to limitations in daily activities. The management of gout can be conducted not only through pharmacological therapy but also through non-pharmacological approaches, one of which is the use of herbal plants such as soursop leaves (Annona Muricata Linn), which are known to contain flavonoids and antioxidants that can inhibit uric acid formation. This study aimed to determine the effect of soursop leaf tea infusion on reducing uric acid levels among the elderly at Posyandu Kenangan Baru, Percut Sei Tuan District, Deli Serdang Regency. This study employed a quantitative pre-experimental design using a one group pretest–posttest design. A single intervention group was used in this study. A total of 25 respondents were selected using purposive sampling techniques. Data analysis was performed using the Wilcoxon Signed-Rank Test. The results of the Wilcoxon Signed-Rank Test showed a p-value of 0.000 (p < 0.05), indicating a significant difference in uric acid levels before and after the intervention. These findings demonstrate that the administration of soursop leaf tea infusion had a significant effect on reducing uric acid levels among the elderly. The administration of soursop leaf tea infusion is effective in reducing uric acid levels in elderly patients with gout and can be applied as an alternative non pharmacological therapy in the management of gout in healthcare facilities.